Going to the dentist. - Shooter, Howard (New York : DK, 2007)
Follows a little girl as she has a check-up at the dentist and learns about good oral hygiene.
Cover title.
1.7
K-3
Keywords: Children -- Preparation for dental care -- Juvenile literature; Dentistry -- Juvenile literature; Teeth -- Care and hygiene -- Juvenile literature; Dental care; Dentistry; Teeth -- Care and hygiene; Dental care; Dentistry